From Classroom to Capitol: Building Advocacy Capacity Through State-Level Advocacy Experiences. Issue 6 (November 2016) - Rivera, Lydia; Starry, Bethany; Gangi, Catherine; Lube, Lauren M.; Cedergren, Anders; Whitney, Emily; Rees, Keely
This commentary provides insight from Community Health Education and Master of Public Health students on the benefits of participating in a state-level Advocacy Experience and provides a theoretical framework for increased advocacy intention among students as a result of participating in a state-level Advocacy Experience. Providing students the opportunity to translate what they learn about advocacy in the classroom into advocacy in action with policy makers is vital to the career development of our future health education professionals and is key to increasing advocacy capacity within our profession. This article builds on previous work from emerging public health professionals highlighting the role of policy advocacy in professional development and provides additional perspectives from the next generation of health education specialists.